Implementation Of Government Accounting Standards And Internal Control In Improving The Quality Of Financial Reports At SMK Negeri 1 Patumbak - Sabar Jaya Mendrofa; Oktarini Khamilah Siregar; Agus Tripriyono (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study is motivated by the importance of accountability and transparency in public financial management, particularly in the vocational education sector. The objective of the research is to examine the implementation of Government Accounting Standards (SAP) and the Government Internal Control System (SPIP), as well as their contribution to improving the quality of financial reports at SMK Negeri 1 Patumbak. The research employs a descriptive qualitative approach using interviews, observations, and documentation. Key informants consist of the principal, vice principals, treasurer, and school operator. Data analysis follows Miles and Huberman’s interactive model, including data reduction, data presentation, and conclusion drawing. The findings indicate that the application of SAP at SMK Negeri 1 Patumbak refers to Government Regulation No. 71 of 2010 through the use of an online-based financial reporting application. This enhances efficiency, transparency, and accuracy of reporting. However, limited understanding of accrual-based accounting among human resources remains a challenge. The implementation of SPIP has been carried out through function segregation, authorization, and transaction documentation, yet routine internal audits have not been conducted, resulting in less-than-optimal oversight. Overall, the application of SAP and SPIP has positively impacted the quality of the school’s financial reports, as reflected in improved relevance, reliability, comparability, and transparency. Nevertheless, strengthening human resource capacity, increasing training intensity, and ensuring consistency in audit practices are required to further enhance report quality and maintain accountability within the school.